Compensation Following Bilateral Vestibular Damage - Yates, Bill J.; McCall, Andrew A. (Frontiers in Neurology, 2011)
Bilateral loss of vestibular inputs affects far fewer patients than unilateral inner ear damage, and thus has been understudied. In both animal subjects and human patients, bilateral vestibular hypofunction (BVH) produces a variety of clinical problems, including impaired balance control, inability to maintain stable blood pressure during postural changes, difficulty in visual targeting of images, and disturbances in spatial memory and navigational performance. Experiments in animals have shown that non-labyrinthine inputs to the vestibular nuclei are rapidly amplified following the onset of BVH, which may explain the recovery of postural stability and orthostatic tolerance that occurs within 10 days. However, the loss of the vestibulo-ocular reflex and degraded spatial cognition appear to be permanent in animals with BVH. Current concepts of the compensatory mechanisms in humans with BVH are largely inferential, as there is a lack of data from patients early in the disease process. Translation of animal studies of compensation for BVH into therapeutic strategies and subsequent application in the clinic is the most likely route to improve treatment. In addition to physical therapy, two types of prosthetic devices have been proposed to treat individuals with bilateral loss of vestibular inputs: those that provide tactile stimulation to indicate body position in space, and those that deliver electrical stimuli to branches of the vestibular nerve in accordance with head movements. The relative efficacy of these two treatment paradigms, and whether they can be combined to facilitate recovery, is yet to be ascertained.